Kajian penyakit oleh kulat Ganoderma pada pokok palma sekitar unimas - Herman Hadafi, Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2003)
Ganoderma sp. is one of pathogenic fungi which can cause damage on palms. Study was done to identify the status ofGanoderma sp infection. on palm trees in UNJMAS's campus. Morphological studies on Ganoderma sp. were done by observing the stnlcture and texture of the fimgal fruiting body. Physiological studies were done to determine the suitable _growth medium, temperature and pH for the growth of Ganoderma sp .. Research on the interaction between Ganoderma sp. with antagonist fungi such as Penicillium sp., Fusarium sp. and Trichoderma sp. was aLm done. Result shows that the mycelium of Ganoderma sp. grew faster on CMA but more mycelium was formed on PDA. The mycelia grew rapidly on temperature of 25°C - 30 °C and at pH between 7.0 - 8.0. There were also interaction by the antagonist fungi to the growth ofGanoderma sp ..